2003
DOI: 10.1002/ana.10593
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drug use in nursing home admissions

Abstract: Although 1 of 10 nursing home residents is taking an antiepileptic drug (AED), no study to our knowledge has determined whether most residents are already receiving AED treatment when they are admitted or are given these drugs afterward. That differentiation was the focus of this study. The study group consisted of 10,318 residents, 65 years and older, admitted to 510 nursing homes located throughout the United States during the first quarter of 1999. AED prevalence at admission was 7.7%; three fifths had an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 44 publications
1
42
1
1
Order By: Relevance
“…6 Antiepileptic drugs (AEDs) are used by 2% of community-dwelling and by 4-11% of the institutionalized elderly. [7][8][9][10][11] Carbamazepine and gabapentin are the most commonly used AEDs in Europe, 10,12 and phenytoin and gabapentin are the most commonly used in the United States. 13 At the time the present study was designed, carbamazepine was a standard choice for elderly patients in the European Union; however, as cytochrome P450 inducers, carbamazepine and phenytoin interact with many drugs.…”
mentioning
confidence: 99%
“…6 Antiepileptic drugs (AEDs) are used by 2% of community-dwelling and by 4-11% of the institutionalized elderly. [7][8][9][10][11] Carbamazepine and gabapentin are the most commonly used AEDs in Europe, 10,12 and phenytoin and gabapentin are the most commonly used in the United States. 13 At the time the present study was designed, carbamazepine was a standard choice for elderly patients in the European Union; however, as cytochrome P450 inducers, carbamazepine and phenytoin interact with many drugs.…”
mentioning
confidence: 99%
“…A closer examination of AED use in nursing homes revealed that approximately 7% of residents are receiving AEDs at the time of admission, but, surprisingly, approximately 3% have an AED newly prescribed after admission (9). Phenytoin is the most commonly used AED in nursing homes.…”
mentioning
confidence: 99%
“…12 However, in our study, the vast majority of persons with an epi/sz diagnosis had one of the specified neurologic conditions (table 2). Only 4.8% of patients with epi/sz (data not shown) had none of the evaluated neurologic conditions.…”
Section: Resultsmentioning
confidence: 49%
“…A previous nationwide study found that the prevalence of epilepsy on admission to NHs was 5.83%. 12 The total number of residents with epi/sz was .90,000 in our data for each year and represents a large proportion of all persons with epilepsy in the United States.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation